Subnaphthalocyanines as Electron Acceptors in Polymer Solar Cells: Improving Device Performance by Modifying Peripheral and Axial Substituents. Issue 24 (10th April 2018) - Duan, Chunhui; Guzmán, David; Colberts, Fallon J. M.; Janssen, René A. J.; Torres, Tomás
Abstract: A new class of subnaphthalocyanines bearing various peripheral and axial substituents have been synthesized for use as electron acceptors in solution‐processed bulk‐heterojunction polymer solar cells. The resulting solar cells exhibit modest photovoltaic performance with contributions from both the polymer donor and subnaphthalocyanine acceptor to the photocurrent. Abstract : A new class of subnaphthalocyanines bearing various peripheral and axial substituents have been synthesized for use as electron acceptors in solution‐processed bulk‐heterojunction polymer solar cells. The resulting solar cells exhibit modest photovoltaic performance with contributions from both the polymer donor and subnaphthalocyanine acceptor to the photocurrent (see figure).